Electrocoagulation for suspended solid removal in domestic wastewater treatment - Rahmalan, Muhammad Taufiq (2009)
The treatment of wastewater has become an absolute necessity. Innovative, cheap and effective methods of purifying and cleaning wastewater before discharging into any other water systems are needed. A wide range of wastewater treatment techniques are known which include biological processes and physicochemical processes. A host of promising techniques based on electrochemical technology are being developed and existing ones are improved that require less chemical additions. The present study was conducted to investigate the applicability of the electrocoagulation technique for the treatment of domestic wastewater at the UTM Oxidation Pond effluent as a case study. The combination effects of current, pH and treatment time to the efficiency of the electrocoagulation process for the removal of suspended solids from the domestic wastewater showed that only current(C) and treatment time (t) have correlation with each other. The optimum batch technique operational conditions for the electrocoagulation application to remove suspended solids from domestic wastewater is current value is 0.5A – 0.65A within 46 until 60 minutes treatment time. These optimum conditions have an optimum result with 120 minutes settling time. Meanwhile the optimum conditions for batch technique were applied to the continuous flow method while resulted in between 80-83% efficiencies of suspended solid removal from the wastewater.